Kedudukan Hukum dan Tanggung Jawab Pendiri Perseroan Terbatas (PT) dalam Proses Perjanjian Kredit - Muhammad Rizal Pratama (LPPM Universitas Ekasakti Padang, 2023)
In practice, there are often irregularities committed by the founders of the Limited Liability Company (PT) which are inconsistent with the purpose of the PT he founded. This not only has the effect of hampering the development of the company itself, it is also detrimental to the creditors. The purpose of this research is to find out and analyze the realization of the responsibilities of the founders of a Limited Liability Company (PT) in a credit agreement and to find out and analyze the legal remedies that can be taken if there is an abuse of the establishment of the Company. This type of research uses empirical and normative aspects with explanations. The results of the study state that the position of the Founder of a Limited Liability Company (PT) is only as a shareholder, and the founder is not responsible for any engagements that have been made by the company. And founders or shareholders cannot be burdened with the obligation to pay losses suffered by the company in excess of the value of the shares that have been taken. However, at PT AJP, who is a thorough researcher, the founder still participates in the credit agreement process that the PT does because the founder of PT AJP, who is a research researcher, is part of the PT's organs, namely as a Director